Successful and Unsuccessful Offensive Sequences Ending in a Shot in Professional and Elite Under-16 Basketball - Alsasua, Roberto (J Hum Kinet, 2018)
Following observational methodology, we analyzed successful and unsuccessful offensive attacks by professional and elite under-16 (U16) basketball players in Spain using an adapted ad hoc observation instrument designed to study efficiency in basketball. We identified both similarities and differences between how players from both categories built their attacks. The synchronic statistical analysis based on frequency counts showed that shots were more efficient in professional basketball and that U16 basketball was less static and had a higher frequency of fast breaks. Diachronic analysis, which consisted of T-pattern detection using Theme software, allowed us to identify characteristic successful and unsuccessful offensive sequences in professional and elite U16 basketball. These results have practical implications as they can be used to design training drills and prepare for competitions in U16 and professional basketball.